Bilateral Gastrocnemius Flap For Harlequin Defects Around The Knee - Chabra, Tarun; Hari, Venkatramani; SR, Sabapathy (Jurnal Plastik Rekonstruksi, 2019)
Background : Tibial plateau fractures (especially bicondylar Schatzker type 5 and type 6) are a result of high energy trauma. Along with bony component, soft tissue injury is a major determinant in the treatment and final outcome. Bicondylar fractures needs bicolumnar fixation and as such require separate approaches: postero-medial and lateral incisions. The soft tissue of the proximal tibia swells significantly after the injury, coupled with extensive soft tissue dissection during fixation this can lead to subsequent wound breakdown and infection along either side of the proximal tibia which resembles “harlequin eyes”. This study describes outcome of management of post operative soft tissue complications following bicolumnar fixation of proximal tibia with medial and lateral gastrocnemius flap. Method : Three patients who had bilateral soft tissue necrosis at surgical incision sites treated with debridement and bilateral gastrocnemius flaps between January 2016 and December 2017 were included in this study. The mean age was 38 years (range 18–50 years) and the mean duration of follow-up was 10 months. Outcome assessments included the condition of the flap and fracture healing time. Result : All fractures united after surgery. There were no soft tissue complications and all flaps healed well. The mean bony union time was 6 months. Conclusion: Our technique of covering soft tissue loss at surgical site on medial and lateral side of proximal tibia with bilateral gastrocnemius flap in the same setting is a reliable and safe surgical method for these conditions.